Efficacy of Chemotherapy in Survival of Stage I Nasopharyngeal Carcinoma - Ma, Jia-Lin; Huang, Shi-Ting; Jiang, Yan-Ming; Pan, Xin-Bin (Frontiers in Oncology, 2021)
Purpose: To identify whether chemoradiotherapy improves survival of stage I nasopharyngeal carcinoma (NPC). Materials and methods: NPC patients were extracted from the Surveillance, Epidemiology, and End Results database between 2010 and 2015. Pathologically confirmed stage T1N0M0 (the 7th edition AJCC) were investigated. Overall survival (OS) and cancer-specific survival (CSS) were compared between the radiotherapy and chemoradiotherapy groups using the Kaplan-Meier method and propensity score matching (PSM) analyses. Results: This study included 91 (40.27%) patients in the chemoradiotherapy group and 135 (59.73%) patients in the radiotherapy group. Before PSM, chemoradiotherapy was associated with worse 3-year OS (74.31% vs 87.23%; P = 0.025) and 5-year OS (64.28% vs 83.12%; P = 0.001) compared to those associated with radiotherapy. Similarly, chemoradiotherapy showed worse 3-year CSS (87.01% vs 96.97%; P = 0.028) and 5-year CSS (80.39% vs. 96.97%; P = 0.002) than those of radiotherapy. After PSM, chemoradiotherapy revealed worse 5-year OS (63.10% vs. 82.49%; P = 0.031) and CSS (80.95% vs. 93.70%; P = 0.016) than radiotherapy. The multivariate regression analysis revealed that chemoradiotherapy was an independent risk prognostic factor for OS and CSS before and after PSM. Conclusion: Radiotherapy alone is recommended for stage I NPC patients.